MetaTT - A Metamodel Based Approach for Writing Textual Transformations - Ledo, Anderson; Ramalho, Franklin; Melo, Natã (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
We present MetaTT, a Metamodel based approach for writing Textual Transformations. It is an operational and stepwise approach for the construction of model-to-text generators in the context of Model-Driven Development. It relies on a particular architecture that fosters good transformation design and generates the main artifacts of a model-to-text generator, requiring the developer to take some design decisions and basically fulfill simplified templates. We evaluate its use by means of its application in the construction of a variety of instances of the problem, and we compared the generators built with and without MetaTT, taking into consideration the size and complexity of the metamodels being tackled.